Correction Hypocalemic Patients with Potassium Chloride in ICU of Dr. Hasan Sadikin Hospital Bandung in Januari–Februari 2014 - Hidayat, Dede A; Fuadi, Iwan; Sitanggang, Ruli H. (Perdatin Pusat, 2015)
Hypokalemia (Potassium plasma level <3.5 mEq/L) is the most common electrolyte imbalance found in the intensive care unit (ICU). Major etiologies of hypokalemia in ICU setting were related to low intake, gastro intestinal tract (GIT) disturbance, renal impairment, diuretic administration, insulin therapy and severe infection, which ranging from asymptomatic to the most severe symptom and causing death.This prospective observational study was conducted in the ICU of Dr. Hasan Sadikin Hospital Bandung from January to February 2014 with result 33 out of 105 admitted patients (31.4%) suffered from hypokalemia.From our observation, there was 17 patients (51.5%) with mild hypokalemia, 13 patients (39.4%) with moderate hypokalemia and 3 patients (9.1%) with severe hypokalemia. Correction with intravenous potassium chloride was given with improvement in 9 patients (53%) in mild hypokalemia group, 3 patients (23.1%) in moderate hypokalemia group but unfortunately no significant change was found in severe hypokalemia group after the correction. Complications were found mostly in geriatric patients with severe hypokalemia.The conclusion of this study is that from all patients admitted to the ICU of Dr. Hasan Sadikin Hospital Bandung from January ̶ February 2014, the incidence of hypokalemia was 31.3% (33 patients) with improvement occurred in 12 patients (36.4%) but 21 patients (63%) revealed no improvement after potassium chloride correction with worsening condition.